The student Bible atlas - Dowley, Tim.; Scott, Richard, 1957-; Three's Company (Firm) (Nashville, Tenn. : Thomas Nelson, 1996)
Describes and details the many journeys included in the Bible and puts into context the important geographical places mentioned.
Title from cover.
"Worldwide coedition organised and produced by Angus Hudson Ltd, Mill Hill, London."
Includes index.
Keywords: Bible -- Geography -- Maps